Persuasive languages on political billboard of the 2024 Indonesian General Election in Padang City West Sumatra, Indonesia - Fachri Bintang Farhan; Ike Revita; Oktavianus Oktavianus (Cogent Arts & Humanities)
Persuasive languages have advantages and strengths in influencing the public to achieve goals. Therefore, people use persuasive language widely in various communication events. In this regard, this study attempts to research the strategic role of persuasive language used by politicians in the City of Padang who are running to become members of the People’s Representative Council and Regional Representative Council, as well as the presidential and vice presidential candidates they nominate. The researchers conducted the study using a linguistic landscape and a pragmatic approach. The data for this study are two hundred sub-texts segmented from billboards of the candidate of the members of the Indonesian House of Representatives (DPR), the Regional People’s House of Representatives (DPRD), and the Regional Representative Council (DPD) in the period of 2024–2029. The researchers collected the data by capturing photographs of billboards in Padang City. The results of the analysis reveal that the landscape of persuasive languages in political billboards in Padang City consists of nine types. Meanwhile, the linguistic landscape of persuasive languages of one billboard consists of three parts: introducing the parties, the main message, and additional information. The languages used are Indonesian, Minangkabau language, English, and Arabic. Regarding pragmatics, the politicians deliver the message through direct and indirect literal speech acts of various kinds. The politicians also put politeness systems and deixis in their language on the billboards.